A plan of the island of Cape Britain reduced from the large survey made by the orders and instructions of the right honorable the Lords Commissioners for Trade and Plantations / by Samuel Holland esqr. surveyor general of the northern district of America &c. with the assistance of his deputies. - Holland, Samuel, 1728-1801
Signed at lower right: By Ensign George Sproule of the 59th Regt. deputy surveyor 19th: April 1767.; Notation at lower left: The soundings and naval observations were taken by Lieutenant Henry Morvat of His Majesty's Armed Ship the Canceaux with the assistance of the gentlemen under his directions.; Finished, colored topographical map showing details along the coast and also identifying parish boundaries and other details.; Table gives details of acreage of the different parishes.